ASPECTS OF POPULATION STRUCTURE OF Pseudotolithus typus, Lutjanus goreensis AND Sphyraena afra FROM LAGOS COASTAL WATERS, LAGOS STATE, NIGERIA - AKINBOBOLA, A.P; FAKOYA, K.A. (Nigerian Journal of Fisheries, 2021)
Information on the population structure of Pseudotolithus typus, Lutjanus goreensis and Sphyraena afra in Lagos State, Nigeria is scanty. The present study investigates their size distributions in terms of lengths and weights, asymptotic length (L), length at first maturity (Lm), maximum length at capture (Lmax), length at maximum yield (Lopt), ratios of Lmax/L and Lopt/ L . A total of 222 P. typus, 182 L. goreensis, and 93 S. afra were collected from the trawlers landing sites at Kirikiri Lighter Terminal II from April to September 2019. The mean total length for P. typus, L. goreensis, and S. afra was 37.54±14.65cm, 36.03±7.64cm, and 68.71±17.39cm while body weights (g) were 821.63±60.68, 838.24±68.56, and 1675.60±1470.90. The estimate from POPDYN spreadsheet showed that P. typus, L. goreensis, and S. afra had an L of 102.8cm, 61.6cm, and 163.3cm respectively. The slope (b) values for S. afra, P. typus, and L. goreensis were 2.709, 2.560, and 2.507 respectively denoting a negative allometry growth pattern. P. typus and L. goreensis had K values of 1.55±0.56 and 1.79±0.84 respectively, S. afra had 0.52±0.06. In conclusion, the results indicated that all the fish becomes vulnerable to capture before spawning, a feature of growth overfishing. Hence, fishers should embrace gear selectivity to conserve these fishes.